Economic Significance Of Pilgrimage (In The Example Of Pilgrimage Of Namangan Region) (Global Scientific Review, 2025)
This article analyzes the economic importance of shrines. It was analyzed that the contribution of shrines to the economic development of the region is important, not only religiously and spiritually. During the research, the economic activity around the shrines, trade, hotel services (home hotel economy), and the economic impact of religious tourism on the society are shown.